The Rac Activator DOCK2 Mediates Plasma Cell Differentiation and IgG Antibody Production - Ushijima, Miho; Uruno, Takehito; Nishikimi, Akihiko; Sanematsu, Fumiyuki; Kamikaseda, Yasuhisa; Kunimura, Kazufumi; Sakata, Daiji; Okada, Takaharu; Fukui, Yoshinori (Frontiers in Immunology, 2018)
A hallmark of humoral immune responses is the production of antibodies. This process involves a complex cascade of molecular and cellular interactions, including recognition of specific antigen by the B cell receptor (BCR), which triggers activation of B cells and differentiation into plasma cells (PCs). Although activation of the small GTPase Rac has been implicated in BCR-mediated antigen recognition, its precise role in humoral immunity and the upstream regulator remain elusive. DOCK2 is a Rac-specific guanine nucleotide exchange factor predominantly expressed in hematopoietic cells. We found that BCR-mediated Rac activation was almost completely lost in DOCK2-deficient B cells, resulting in defects in B cell spreading over the target cell-membrane and sustained growth of BCR microclusters at the interface. When wild-type B cells were stimulated in vitro with anti-IgM F(ab’)2 antibody in the presence of IL-4 and IL-5, they differentiated efficiently into PCs. However, BCR-mediated PC differentiation was severely impaired in the case of DOCK2-deficient B cells. Similar results were obtained in vivo when DOCK2-deficient B cells expressing a defined BCR specificity were adoptively transferred into mice and challenged with the cognate antigen. In addition, by generating the conditional knockout mice, we found that DOCK2 expression in B-cell lineage is required to mount antigen-specific IgG antibody. Theses results highlight important role of the DOCK2-Rac axis in PC differentiation and IgG antibody responses.